Three-dimensional modelling of turbine wake interactions at a tidal stream energy site. (February 2020) - N, Michelet; N, Guillou; G, Chapalain; J, Thiébot; S, Guillou; Goward Brown, A.J.; Neill, S.P.
Highlights: Turbine wake interactions were simulated in the tidal stream energy site of the Fromveur Strait. This evaluation was conducted by implementing the Actuator Disk method in the 3D model ROMS. Predictions of the undisturbed flow field were assessed against ADCP measurements. The Fromveur Strait exhibited asymmetries in tidal current magnitude and direction. Turbines lateral spacing was reduced to minimise wake interactions due to current misalignment. Abstract: One of the biggest uncertainties in tidal stream energy resource assessment is how tidal energy conversion, particularly at large scale, will interact with the resource. As few arrays are currently operational, data collected from these developments tends to be commercially sensitive. Therefore, array interaction with the resource is generally assessed using numerical models. A fully three-dimensional numerical approach based on Actuator Disk theory was implemented into the Regional Ocean Modelling System (ROMS) to simulate the energy extraction by tidal stream turbines. Emphasis was placed on wake interactions and cumulative effects of individual devices on energy extraction at array scale. This model was applied at the tidal stream energy site of the Fromveur Strait (western Brittany, France) considering an array of horizontal-axis turbines of 10-m diameter, matching the device technology currently operating in the Strait. Two tidal energy metrics were considered to describe asymmetries in tidal current magnitude and direction. The area with reduced asymmetry in current magnitude was selected to implement the turbine array. A nested grid technique was adopted to cascade processes from the regional scale to the high-resolution local farm domain. The computation was conducted over the inner-nested array domain covering the tidal farm with horizontal and vertical resolutions of 1 m, matching the 1/10th turbine diameter (D) recommended to resolve velocity and turbulence intensity along device wakes. The array layout initially followed recommended staggered configurations with longitudinal and lateral spacings of 10D and 5D, respectively. However, during mean spring tidal conditions, the misalignment of peak flood currents induced significant wake interactions that reduced the array output by about 15% in comparison to peak ebb. These interactions were investigated to adapt array layouts, minimise wake interactions, and optimise the energy conversion. By reducing the lateral spacing between devices to 3D (measured centre to centre rather than tip to tip), the flood ebb asymmetry in energy extraction was lowered from 15% to 2%.